Carbonitridation Pyrolysis Synthesis of Prussian Blue Analog‐Derived Carbon Hybrids for Lithium‐Ion Batteries. (15th September 2021) - Wang, Yisha; Chen, Ruixuan; Ang, Edison Huixiang; Yan, Yan; Ding, Ying; Ke, Longwei; Luo, Yan; Rui, Kun; Lin, Huijuan; Zhu, Jixin
Abstract: Cost‐effective nanostructured carbon hybrids have received global attention in sustainable energy research due to their stable structure and high conductivity. Herein, the nickel‐cobalt nanoparticles embedded carbon nanotube hybrid (NCCH) derived from Prussian blue analogs (PBAs) has been prepared by a carbonitridation pyrolysis process. Simultaneously, the uniform NCCHs interweave to form a conductive structure. The fascinating architecture offers abundant active sites and enhanced electronic conductivity when served as an anode material in lithium‐ion batteries. As a consequence, the resulting NCCH exhibits excellent cell behaviors with a high reversible capacity and remarkable rate capability. Equally important, the study provides a unique insight into the development of high‐performance carbon hybrids electrodes derived from PBAs. Abstract : The nickel‐cobalt nanoparticles embedded carbon nanotube (CNT) hybrid derived from Prussian blue analog is successfully designed through a facile carbonitridation pyrolysis process. The hierarchical structure offers abundant active sites, accelerates ion diffusion, and enhances electronic conductivity. Consequently, the resulting CNT hybrid exhibits excellent electrochemical performance when used as an anode for lithium‐ion batteries.